“Sincerely Held Religious Beliefs”: Media Representation and Rhetorical Strategy During Arizona’s SB 1062 Controversy - Elizabeth Lowry (European Journal of American Studies)
In February 2014, the Governor of Arizona was given one week to decide whether or not to veto SB 1062, a controversial bill that would allow business owners to refuse service to clients whose lifestyle choices offended them. During that week, the bill was widely reported upon, and became a subject of national debate. I draw on rhetorician Kenneth Burke’s theory of dramatism to analyze oppositional media discourses around SB 1062—in particular the conservative Christian strategy to frame SB 1062 as a matter of religious freedom. To do so, I consider various components of rhetorical exigency such as the role of public participation in political debate, narrative-building, and a process that Crick and Gabriel refer to as “sensual-aesthetic disruption.” I argue that it is not only a fondness for oppositional rhetorics, but the promotion of individualism and a lack of appreciation for the idea of the common good that cultivated a political climate that allowed SB 1062 to initially gain support.